Fabrication and Tailoring Structural, Optical, and Dielectric Properties of PS/CoFe2O4 Nanocomposites Films for Nanoelectronics and Optics Applications - Abbas, Mohammed H.; Ibrahim, Hamed; Hashim, Ahmed; Hadi, Aseel (Transactions on electrical and electronic materials, 2024)
Cobalt-based ferrite nanocomposites have been envisioned as the most promising materials to be utilized in various optical and electronic devices, including transistors, electronic gates, and photovoltaic cells. Here, a casting method is used to fabricate polystyrene/cobalt ferrite (PS/CoFe 2 O 4 ) nanocomposite films (NFs) with different CoFe 2 O 4 nanoparticle contents (0–6.3 wt%), followed by characterizing their chemical, microstructural, optical, and dielectric properties. The absorbance of PS/CoFe 2 O 4 NFs increases to 70% and the transmittance decreases to 75% at a wavelength of λ = 580 nm when the CoFe 2 O 4 content increases to 6.3 wt%. Moreover, the absorption coefficient increases from 378 cm −1 for pure PS to 630 cm −1 for NFs with CoFe 2 O 4 content of 6.3 wt% at a photon energy of 4.44 eV. The energy gap of allowed and forbidden indirect transitions is reduced from 3.3 to 2.4 eV and 3.2 to 2 eV when the nanoparticle content increases from 0 to 6.3 wt%. Mean while, the extinction coefficient and refractive index show increasing trends at λ = 880 nm, increasing from 0.5 × 10 –3 to 2 × 10 −3 and 1.8 to 2.5, respectively. It is found that the real and imaginary parts of the dielectric constant are enhanced with increasing the CoFe 2 O 4 content.The results of AC electrical properties indicate that the corresponding electrical conductivity and dielectric constant increase by about 58% and 35% with the increase in the CoFe 2 O 4 content at a frequency of 100 Hz. Therefore, the PS/CoFe 2 O 4 NFsmay pave the way for potential applications in nanoelectronics and nanodevices.